2014
DOI: 10.1016/j.rbmo.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Family association study between tumour necrosis factor a gene polymorphisms and polycystic ovary syndrome in Han Chinese

Abstract: Polycystic ovary syndrome (PCOS) is a complex disease involving genetic and environmental components. Tumour necrosis factor a (TNFa) is a proinflammatory cytokine in the pathogenesis of PCOS. The genetic association between polymorphisms of TNFa gene and PCOS was investigated. A family based study was conducted with 216 family trios (648 participants) having a proband with PCOS. Transmission disequilibrium test (TDT) was used to analyse the association between two single nucleotide polymorphisms (SNP) (rs1799… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Recent investigations have shown that rs1799964 polymorphism in the promoter region of the TNF-α gene could be associated with PCOS [ 1 , 3 , 16 ]. In contrast, several studies have revealed a lack of direct involvement of rs1800629 polymorphism of the TNF-α gene in PCOS patients in South Indian, Turkish, and Australian populations [ 2 , 3 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent investigations have shown that rs1799964 polymorphism in the promoter region of the TNF-α gene could be associated with PCOS [ 1 , 3 , 16 ]. In contrast, several studies have revealed a lack of direct involvement of rs1800629 polymorphism of the TNF-α gene in PCOS patients in South Indian, Turkish, and Australian populations [ 2 , 3 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a major cause of female infertility, affecting 6–10% of women during reproductive age; moreover, it is one of the most prevalent endocrine disorders [ 1 ]. This syndrome is associated with increased risks of obesity, type 2 diabetes mellitus, hyperinsulinemia, insulin resistance, cardiovascular disease, and dyslipidemia [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, inheritance patterns, characterized by complex polygenic traits, further complicate the identification of genetic factors. Genetic susceptibility studies of PCOS have focused on genes related to the metabolism of adipose tissue and steroid hormones and the release and action of gonadotropin and insulin and inflammatory cytokine genes [3][4][5][6][7][8]. However, it is difficult to establish which genes are involved due to a wide range Capsule This study demonstrates that TGF-β1 gene SNPs are associated with PCOS development (rs1800469 and rs4803457) and with PCOS characteristics in Korean women (rs1800469 and rs2317130), as assessed by laboratory and clinical measurements.…”
Section: Introductionmentioning
confidence: 99%